2003
DOI: 10.2176/nmc.43.375
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Diffuse Type Brainstem Gliomas: Analysis of 40 Autopsy Cases

Abstract: Diffuse type brainstem glioma is one of the most malignant types of brain tumors and the prognosis is extremely poor. The proliferative potential of these tumors is presumed to be very high, but there is little information about the cell kinetics of brainstem glioma because surgical resection is rarely performed. The histological grade, tumor spread, growth potential, and prognosis were evaluated in 40 autopsy cases of diffuse type brainstem glioma. To quantify the growth potentials of individual tumors, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…MRS studies of gliomas in the adult population showed that increased levels of tCho, decreased metabolite ratios of NAA to tCho (NAA/ tCho) and Cr to tCho (Cr/tCho), and increased levels of lipids are indicators of malignant degeneration. 15 -22 DIBSGs are believed to progress to higher-grade gliomas (often glioblastomas at autopsy 6,8 ), consistent with deterioration and death of 90% of patients within 2 years after initial diagnosis. 3 Therefore, our general hypothesis was that metabolic progression may parallel disease progression and could be exploited (1) to assess disease …”
Section: Discussionmentioning
confidence: 99%
“…MRS studies of gliomas in the adult population showed that increased levels of tCho, decreased metabolite ratios of NAA to tCho (NAA/ tCho) and Cr to tCho (Cr/tCho), and increased levels of lipids are indicators of malignant degeneration. 15 -22 DIBSGs are believed to progress to higher-grade gliomas (often glioblastomas at autopsy 6,8 ), consistent with deterioration and death of 90% of patients within 2 years after initial diagnosis. 3 Therefore, our general hypothesis was that metabolic progression may parallel disease progression and could be exploited (1) to assess disease …”
Section: Discussionmentioning
confidence: 99%
“…When tissue from diagnostic biopsy or postmortem examination is obtained, the majority of these neoplasms are found to be high-grade astrocytomas. 14,15 High-grade astrocytomas, in particular glioblastoma multiforme, are among the most vascularized human tumors. 16 Histologically identical neoplasms arising outside the brainstem in children and adults have an increased predisposition to develop intratumoral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…At autopsy, most lesions have progressed to higher-grade tumors such as anaplastic astrocytoma or glioblastoma. 4,[15][16][17][18][19] Therefore, biochemical changes that are associated with malignant transformation can be studied by serial MR spectroscopy in these tumors. We observed metabolic changes indicative of malignant transformation, reported elsewhere, 20 that have been also previously reported by Laprie et al 21 and Thakur et al 22 for this patient population.…”
Section: Citrate In Pediatric Brain Tumorsmentioning
confidence: 99%